2010
DOI: 10.1016/j.ejso.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Postresection survival outcomes of pancreatic cancer according to demographic factors and socio-economic status

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T A C C E P T E D ARTICLE IN PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
11
1
1
Order By: Relevance
“…However, in patients with resectable tumors, SES was no longer a relevant variable for survival. This was also found in a case series of 117 patients in Germany in which the SES was obtained from individual patients[22]. …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, in patients with resectable tumors, SES was no longer a relevant variable for survival. This was also found in a case series of 117 patients in Germany in which the SES was obtained from individual patients[22]. …”
Section: Discussionsupporting
confidence: 59%
“…These results confirm findings in other studies in which pancreatic cancer patients with lower SES tend to have worse survival and are less likely to receive adequate treatment (Table 4). In the two series reporting on patients who underwent resection the results are contradictory: the Lim paper [21] (n = 396 patients) describes lower survival in the low SES group, whereas in the Kuhn paper [22] (n = 117 patients) no effect was found.…”
Section: Discussionmentioning
confidence: 99%
“…11,28 Pancreatic cancer patients with a low SES had a higher mortality rate in the United States, whereas SES had no effect on pancreatic cancer mortality in Germany. 7,29 Although the observed differences between the United States and Europe are often explained by the absence of a multipayer health care system in the United States, these data suggest that differences in outcome for several cancer types in Europe are most likely also due to decisional factors that are at least partly related to SES.…”
Section: Discussionmentioning
confidence: 88%
“…This link has been attributed to an increased distance to major medical centers (Gill and Martin, 2002), and a lack of specialization (van Oost et al, 2006). Other studies have shown a lack of effects from socio-economic factors on pancreas cancer treatment outcome (Kuhn et al, 2010). The Surveillance Epidemiology and End Results (SEER) cancer registry data have been to build prognostic models for pancreatic cancer (Baine et al, 2011;Singal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%